2018
DOI: 10.1200/jco.2017.76.7228
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib Plus Intensive Chemotherapy in Children, Adolescents, and Young Adults With Philadelphia Chromosome–Positive Acute Lymphoblastic Leukemia: Results of Children’s Oncology Group Trial AALL0622

Abstract: Purpose Addition of imatinib to intensive chemotherapy improved survival for children and young adults with Philadelphia chromosome-positive acute lymphoblastic leukemia. Compared with imatinib, dasatinib has increased potency, CNS penetration, and activity against imatinib-resistant clones. Patients and Methods Children's Oncology Group (COG) trial AALL0622 (Bristol Myers Squibb trial CA180-204) tested safety and feasibility of adding dasatinib to intensive chemotherapy starting at induction day 15 in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
183
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(198 citation statements)
references
References 45 publications
7
183
2
1
Order By: Relevance
“…This study was approved by the Institutional Review Board of Cincinnati Children's Hospital Medical Center. Patients were treated according to Children's Oncology Group protocols AALL0031, AALL0232, AALL0622, AALL1122, AALL0434, AALL1131 (2 g/m 2 dosing for patients with Down syndrome, 5 g/m 2 dosing for all others), AALL0631 (4 g/m 2 dosing), or AALL0932 (1 g/m 2 dosing, LR‐M arm). Dose reductions or omissions due to toxicity were made for subsequent HDMTX courses per protocol criteria or physician discretion in certain cases.…”
Section: Results and Methodsmentioning
confidence: 99%
“…This study was approved by the Institutional Review Board of Cincinnati Children's Hospital Medical Center. Patients were treated according to Children's Oncology Group protocols AALL0031, AALL0232, AALL0622, AALL1122, AALL0434, AALL1131 (2 g/m 2 dosing for patients with Down syndrome, 5 g/m 2 dosing for all others), AALL0631 (4 g/m 2 dosing), or AALL0932 (1 g/m 2 dosing, LR‐M arm). Dose reductions or omissions due to toxicity were made for subsequent HDMTX courses per protocol criteria or physician discretion in certain cases.…”
Section: Results and Methodsmentioning
confidence: 99%
“…Dasatinib has been employed as first‐line therapy for adult Ph+ ALL to induce deep remission. However, the recent study in children did not show an advantage for dasatinib over imatinib …”
mentioning
confidence: 89%
“…Clinical studies on TKIs for pediatric Ph+ ALL suggested that hematopoietic stem cell transplantation in first CR could be avoided in a subset of children with Ph+ ALL, especially in MRD‐negative patients . However, the higher WBC count at diagnosis conferred a higher risk of late relapse in patients with chemotherapy only, and IKZF1 deletions were also associated with a higher risk of relapse, especially in standard risk patients …”
mentioning
confidence: 99%
“…Treatments and responses are summarized in Figure 1. He achieved molecular remission with induction chemotherapy per the CALGB 10403 protocol [15], followed by consolidation per the AALL0622 protocol [16]. The TKI dasatinib was added to induction therapy, but was subsequently discontinued due to elevated transaminases, which also prompted vincristine and daunorubicin dose reductions.…”
Section: Case Reportmentioning
confidence: 99%